2018
DOI: 10.1007/s11060-018-2967-5
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory brain activity associates with neuroligin-3 expression and predicts progression free survival in patients with diffuse glioma

Abstract: IntroductionDiffuse gliomas have local and global effects on neurophysiological brain functioning, which are often seen as ‘passive’ consequences of the tumor. However, seminal preclinical work has shown a prominent role for neuronal activity in glioma growth: mediated by neuroligin-3 (NLGN3), increased neuronal activity causes faster glioma growth. It is unclear whether the same holds true in patients. Here, we investigate whether lower levels of oscillatory brain activity relate to lower NLGN3 expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 38 publications
8
36
0
Order By: Relevance
“…Patients visiting the VUmc CCA Brain Tumor Center Amsterdam between 2010 and 2017 with suspected diffuse glioma were eligible to participate. Part of this patient cohort has been reported on before (Carbo et al, ; van Dellen et al, ; Derks et al, ). Inclusion criteria were (a) age over 17 years and (b) ability to participate in neuropsychological testing.…”
Section: Methodsmentioning
confidence: 99%
“…Patients visiting the VUmc CCA Brain Tumor Center Amsterdam between 2010 and 2017 with suspected diffuse glioma were eligible to participate. Part of this patient cohort has been reported on before (Carbo et al, ; van Dellen et al, ; Derks et al, ). Inclusion criteria were (a) age over 17 years and (b) ability to participate in neuropsychological testing.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we examined whether our current results were driven by the patients who were previously studied in the presurgical phase of their disease [13]. We did this by dividing the cohort into two subgroups (previously/not previously included by Derks and colleagues) [13]. Cox univariate analyses were then performed in these two groups separately.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This retrospective study cohort, which combined several datasets of patients previously reported on, consisted of de novo glioma patients who underwent tumor resection at the Brain Tumor Center Amsterdam [part of Amsterdam University Medical Center, location Vrije Universiteit (VUmc)] between 2010 and 2017 [13,14]. Inclusion criteria for these studies were (1) age over 17 years, (2) histopathologically confirmed glioma grade II or higher (as defined by the 2016 classification of the World Health Organization [1]), (3) tumor resection as part of their treatment, and (4) no history of neurologic or psychiatric disease.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations